2013
DOI: 10.1186/1741-7015-11-199
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the dose of acute rehabilitation: is there a benefit?

Abstract: Rehabilitation interventions, including physiotherapy and occupational therapy, can improve patient outcomes; however, the optimal duration and frequency of inpatient rehabilitation interventions is uncertain. In a recent randomized controlled trial published in BMC Medicine, 996 patients in two publicly-funded Australian metropolitan rehabilitation facilities were assigned to physiotherapy and occupational therapy delivered Monday through Friday (five days/week control group) versus Monday through Saturday (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…However, increasing the duration and frequency of physical and occupational therapies in inpatients resulted in improved functional independence and better quality of life. 14 An early mobilization protocol significantly reduced patients' total duration of mechanical ventilation and length of stay in the ICU.…”
Section: Emily Castro Is a Critical Care Nurse Educator At Northmentioning
confidence: 99%
“…However, increasing the duration and frequency of physical and occupational therapies in inpatients resulted in improved functional independence and better quality of life. 14 An early mobilization protocol significantly reduced patients' total duration of mechanical ventilation and length of stay in the ICU.…”
Section: Emily Castro Is a Critical Care Nurse Educator At Northmentioning
confidence: 99%
“…This may be related to increased physical activity among patients who received weekend rehabilitation services, reduced functional decline over the weekend because of increased physical activity, or changes in patient perceptions of no longer associating weekends with rest [ 6 ]. However, in spite of the available evidence, many rehabilitation facilities do not provide weekend services [ 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many challenges in post-stroke rehabilitation. For instance, research investigating different therapies (i.e., physical, occupational, perceptual training) has consistently shown that functional outcome is better when therapy doses are higher ( Lohse et al, 2014 ; Ong et al, 2012 ; Parker et al, 2013 ). However, it is not straightforward to deliver high therapy doses in clinical practice ( Bernhardt et al, 2007 ; Lang et al, 2009 ; Ong et al, 2012 ; Otterman et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%